Pseudo Chediak-Higashi anomaly in acute myelomonocytic leukemia - Rao Seema; Kar Rakhee; Saxena Renu (Wolters Kluwer Medknow Publications, 2009)
Pseudo Chediak-Higashi anomaly in acute leukemia is a rarely described entity. The significance of this intriguing morphological finding largely remains unknown, although some authors have predicted a poorer outcome in such cases because of a higher susceptibility to fulminant infections. Our case also had a fatal outcome.